REPETITION TECHNIQUE IN AN EFL SPEAKING CLASS IN ISLAMIC HIGHER EDUCATION IN INDONESIA - Ana Kuliahana; Abdul Gafur Marzuki (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2020)
This research aims at analysing the development of students’ speaking skill in Islamic higher education in Indonesia through repetition technique. This is a CAR (Classroom Action Research) implemented in cyclical process, covering planning, acting, observing, and reflecting. The subject of research was the fourth semester students of EFL speaking class which consist of 25 students. The data were obtained from observation checklist, field notes, questionnaire, and test. They were analysed qualitatively and quantitatively. Quantitative data dealt with teaching-learning process, i.e. students’ participation in the classroom activities. They were gained from students’ achievement tests. The findings revealed that in cycle 1 there were twelve students who achieved minimum criteria of achievement. It means that the classical achievement was 48%. In cycle 2, it showed that there were twenty of students who achieved the minimum criteria of achievement. It means that the classical achievement was 80%. Both classical and individual achievements have met the criteria of success. It can be concluded that the repetition technique is proved to be useful to develop students’ speaking skill.